Penegakan Hukum Terhadap Tindak Pidana Penelantaran Anak Serta Faktor Penghambat di Kepolisian Resor Kupang Kota - George R. H. Fanggi Ello; Rudepel Petrus Leo; Heryanto Amalo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Children are a precious gift from God that is entrusted to parents to be loved and cared for wholeheartedly. A child is someone who is not yet 18 (eighteen) years old, including a child who is still in the womb. Child neglect is the practice of relinquishing responsibility and claims over offspring in an illegal way, this is caused by factors such as economic and social factors, as well as mental illness, among others. A child who is abandoned or abandoned by his parents is called an outcast. Child neglect includes passive torture, which is any state of inadequate attention, whether physical, emotional, or social. The enforcement of criminal sanctions against perpetrators of child neglect must be strictly enforced as in Law Number 35 of 2014 concerning Child Protection. This research is an empirical juridical law research. This study is descriptive and analyzes primary data to determine Law Enforcement against Child Neglect Crimes and Inhibiting Factors in the Kupang City Resort Police. Data collection uses observation, documentation and interview techniques. The results of the study show that (1) Law enforcement against child neglect crimes in the Kupang Kota Resort Police shows a strong commitment to protecting children. However, there are still cases of child neglect due to various factors so that child neglect by parents occurs. (2) Influencing factors include legal and law enforcement factors, economic factors, environmental factors and parental divorce factors that often occur so that cases of child neglect occur.